ANALISIS WACANA KRITIS DEBAT PUBLIK PILKADA DKI JAKARTA PUTARAN KEDUA TAHUN 2017 - Feni Feni; Hotma Simanjuntak; Laurensius Salem (Universitas Tanjungpura, 2019)
Abstract This research was qualitative research that presents the result of critical discourse analysis of DKI Jakarta Gubernatorial Election Final Debate on 2017. This research applied Norman Fairclough’s critical discourse analysis as the major theory. The results are as follows. (1) The language form that represented ideology and power in DKI Jakarta governor candidates’ speeches are classification schemes, dominant words, metaphor, transitivity, active-passive sentences, and positive-negative sentences. Relation and power expressed in euphemism, formality and informality words, modality, and pronouns. Negative-positive evaluations and expressive modality used to represented social identity. Domination, power, and ideology expressed in interruption, enforcing explicitness, and formulation. (2) Interpretation process in DKI Jakarta governor candidates’ speeches contextually shown the events of what happened, who was involved, what relationship that the participants have, and the role of language. Discourse, texts, or events that occurred before the final debate and influenced the DKI Jakarta governor candidates’ speeches represented in interpretation of intertextual context. (3) Explanation process in DKI Jakarta Gubernatorial Election Final Debate explained the change of situation, institution, and social during the debate and after the debate. Keywords: Critical Discourse, Final Debate of DKI Jakarta Gubernatorial Election